The development of mobile historical event storytelling (MHES) framework through expert perspective / Ismassabah lsmail - lsmail, Ismassabah (2019)
Digital Storytelling (DST) has been widely adapted as pedagogical tool for washing, games and entertainment, personal stories, health awareness, knowledge dissemination and historical event. History is the root of human civilization, using DST for relaying the historical event is one useful approach. For a good historical content dissemination, it must adhere to the historical story map. However, the current mobile storytelling (MST) framework lacks the element for historical event dissemination. This research aims to develop a framework for dissemination of historical event by adapting the digital storytelling approach and the historical story map for mobile platform. Two preliminary studies have been conducted (Website Analysis and Survey) to identify the elements and characteristic of mobile DST for historical event. The results of the preliminary studies were used to construct the conceptual framework. For validation purposed, a prototype of a mobile storytelling using the constructed framework was built Two tests were conducted with five experts, Heuristic Evaluation Approach (HEA) (quantitative) and Semi Structured Interview (SSI) (qualitative). The quantitative data from the HEA were analyzed using the Severity Rating Scale (SRS) while the qualitative data from the interview was analyzed using the Thematic Analysis (TA) approach. The first findings from HEA using SRS discover that experts give positive feedback towards the usefulness, understandable and attractiveness components of the multimedia elements in MST on the case study, Perang Badar. The second findings from SSI using TA, is coherence with the first findings, it was found that components of usefulness and understandable also receive a good feedback. Both tests show that the content of historical event is fully delivered to the user as users are able to understand the content. Overall, the development of this framework can support the developer of MST in designing the MST for historical event by applying the content segmentation (story map) and multimedia elements as depicted by the framework. The findings lay a theoretical approach for designing the content of MST using storytelling approach. Thus, further research should focus on the mobile user interface (MUI) for the mobile story telling (MST). Finally, the MST application shall be implemented in various interface layouts especially on small screen display for vast knowledge dissemination.